Carbon dioxide photoreduction using TiO2 sensitized with Co and Cu trimers in aqueous media - Rojas-Sánchez, Carlos E. (2021)
During this investigation, the performance of two titanium dioxide photocatalysts was evaluated in the photoreduction of carbon dioxide in aqueous media. One of the photocatalysts was sensitized with a copper trimer (Cu3(dpa)4Cl2) (dpa = 2.2´-dipyridylamine) and the other was sensitized with a cobalt trimer (Co3(dpa)4Cl2). Using a microwave reactor, the first experimental stage studied the TiO2 sensitization process, which occurs in two successive reactions: in the first one, the TiO2 surface is functionalized with p-Aminobenzoic acid (PABA) which acts as a binding molecule between TiO2 and the respective trimer, while in the second reaction, the metal trimer is anchored. Three levels of temperature, power output, and reaction time were analyzed for each of the two reactions; however, a Taguchi statistical analysis showed no significant differences between the treatments for the selected conditions. Therefore, it was determined that the photocatalyst sensitization process can be performed under the following conditions without affecting the final composition of each catalyst: 70 °C, 100 W, and 5 min in the functionalization stage with PABA and 80 °C, 150 W, and 5 min in the anchorage of the dyes. In the second experimental stage, the synthesized photocatalysts for CO2 photoreduction in aqueous medium was evaluated utilizing a medium-pressure ultraviolet lamp in a photoreactor at atmospheric pressure and at 25 °C. The catalyst with the best performance was the one sensitized with cobalt trimer since it showed a higher production of methane (14.28\ \sfrac{μ mol}{g_{cat}\ h}), and carbon monoxide (32.84\sfrac{μ mol}{g_{cat}\ h}). The copper sensitized catalyst showed no measurable generation of carbon monoxide, and the methane production was considerably lower (6.23\ µmolgcat h). Hydrogen production was important with both catalysts, particularly the catalyst sensitized with the copper trimer (420\ µmolgcat h). No presence of other CO2 reduction products was detected in the liquid phase.